DESIGN AND EVALUATION OF PROPOLIS-HPC/PVP ELECTROSPUN NANOFIBERS FOR POSSIBLE CUTANEOUS APPLICATIONS - İNAL, EBRAR; Esentürk-Güzel I.; KARTAL, MURAT; ALĞIN YAPAR E.; Cavalu S.; ŞEKER İ. T.; İNAL E.; KARTAL M.; Koç R. Ç.; Öztürk R. Y.; Göksu F.; Bölek S.; et al. (My University, 2024)
The aim of the study was to prepare propolis loaded hydroxypropyl cellulose and polyvinyl pyrrolidone (HPC/PVP) nanofibers, suitable for cutaneous applications. LC-HRMS analyses were applied for the identification and quantification of the bio-compounds in the propolis extract. Electrospinning was applied in order to prepare propolis HPC/PVP nanofibers with increasing concentration of propolis 10%, 20% and 30 % (v/v) and subsequently characterized in terms of morphology, wettability, thermal degradation and biological properties. SEM images showed homogenous features of the nanofibers and average diameter between 197.2-268.4 nm, high antioxidant activity, very good biocompatibility and no cytotoxicity. Particularly, with the highest propolis concentration, 30-PE/HPC/PVP nanofiber formulation is a promising alternative to conventional treatments for cutaneous applications.
Keywords: Eczacılık; Temel Eczacılık Bilimleri; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Pharmacology and Therapeutics; Basic Pharmaceutics Sciences; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; General Pharmacology, Toxicology and Pharmaceutics; biocompatibility; electrospinning; hdroxypropylcellulose; nanofibers; polyvinyl pyrollidone; propolis